PENGUJIAN MATERIIL SURAT KEPUTUSAN DIREKSI PT. BANK RAKYAT INDONESIA (PERSERO) TENTANG PEMUTUSAN HUBUNGAN KERJA (Studi Kasus Putusan Mahkamah Agung Nomor 08 P/HUM/2019) - Bahri Pasaribu (Fakultas Hukum universitas Islam Sumatera Utara, 2020)
AbstractTesting the law is a must for assessing whether an assessment-invitation regulation is in accordance with or contradictory to a higher degree of regulation, as well as a certain regulation relating to certain regulations.The problems in this paper are: material testing of a decision of a state-owned enterprise in Indonesian laws and regulations, the trial process of a material test of a state-owned enterprise decision letter in the Decision of the Supreme Court of the Republic of Indonesia Number 08 P / HUM / 2019, consideration of judges in material test of PT. Bank Rakyat Indonesia (Persero) in the decision of the Supreme Court Number 08 P / HUM / 2019This research is descriptive in nature using normative juridical.